Implementation of Capital Deferral Algorithm in Real Distribution Systems Considering Reliability by Managing Major Faults - Yoldas, Yeliz; Onen, Ahmet; Broadwater, Robert; Alan, Irfan (Springer, 2019)
Distribution automation technology plays a key role on power system reliability by providing faster detection, isolating the faulted area and restoring the fault. In this paper, the impacts of distribution automation are considered on radial distribution system in the event of substation transformer bank malfunction at maximum load level with the aim of deferring the big capital investments. The aim of the proposed method is not only to increase physical impact such as the reliability but also to monetize physical measures into significant economic benefits by deferring the overall investment costs. The proposed algorithm is tested with the real distribution system data, and it is shown that it can obtain remarkable economic benefits by deferring the larger capital equipment investments by making smaller investments in distribution automation.
Onen, Ahmet/0000-0001-7086-5112; Yoldas, Yeliz/0000-0002-9821-9339
Keywords: Capital Deferral; Smart Grid Economy; Smart Grid Investments; System Reconfiguration